2022
DOI: 10.3389/fmicb.2022.992582
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of molecular and MALDI-TOF MS identification and antifungal susceptibility of clinical Fusarium isolates in Southern China

Abstract: BackgroundFusarium species are opportunistic causative agents of superficial and disseminated human infections. Fast and accurate identification and targeted antifungal therapy give help to improve the patients’ prognosis.ObjectivesThis study aimed to evaluate the effectiveness of matrix-assisted laser desorption ionisation time of flight mass spectrometry (MALDI-TOF MS) for Fusarium identification, and investigate the epidemiology and antifungal susceptibility profiles of clinical Fusarium isolates in Souther… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 47 publications
0
0
1
Order By: Relevance
“…In our study, our data revealed good applicability with the existing database to classify Fusarium, except F. falciforme were mis-identified as F. proliferatum. Previously studies of Vitek MS and Bruker demonstrated a lower rate of correct identification to the species-level by all methods compared to the present study [ 12 , 21 , 22 ]. Specifically, F. proliferatum and F. verticillioides could not be distinguished and only be identified as a complex group by VITEK MS [ 23 ].…”
Section: Discussioncontrasting
confidence: 72%
“…In our study, our data revealed good applicability with the existing database to classify Fusarium, except F. falciforme were mis-identified as F. proliferatum. Previously studies of Vitek MS and Bruker demonstrated a lower rate of correct identification to the species-level by all methods compared to the present study [ 12 , 21 , 22 ]. Specifically, F. proliferatum and F. verticillioides could not be distinguished and only be identified as a complex group by VITEK MS [ 23 ].…”
Section: Discussioncontrasting
confidence: 72%